RASPBERRY PI UNTUK PENGENDALIAN MIKROKONTROLER PADA PERGERAKAN ROBOT PEMANTAU BERKAKI ENAM - Satria Ramadhan; Lina Lina; Agus Budi Dharmawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Designed system is a six-legged monitoring robot that can be controlled through wireless network. The six-legged robot is designed to use a Raspberry Pi processor and a Basic Stamp 2 microcontroller type. The six-legged robot uses 12 motor servo which each leg has 2 degrees of freedom. The six-legged robot can move using the Wave Gait motion, the Tripod Gait motion, and the Ripple Gait motion that were programmed using a programming language PBASIC. The Raspberry Pi was paired with a Raspberry Pi camera to capture images and a wireless adapter to catch the wireless network signal. The programming language for the six-legged robot is Python. User can give order to the robot to run the motion via Raspberry Pi’s command terminal remotely via a wireless network using PuTTY. User also can capture and record images through a Raspberry Pi’s command terminal. Key wordsBasic Stamp 2, Hexapod, Raspberry Pi, Ripple Gait, Tripod Gait, Wave Gait.